2016
DOI: 10.1073/pnas.1519292113
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of C/D box small nucleolar RNAs in rRNA modification and alternative pre-mRNA splicing

Abstract: C/D box small nucleolar RNAs (SNORDs) are small noncoding RNAs, and their best-understood function is to target the methyltransferase fibrillarin to rRNA (for example, SNORD27 performs 2′-Omethylation of A27 in 18S rRNA). Unexpectedly, we found a subset of SNORDs, including SNORD27, in soluble nuclear extract made under native conditions, where fibrillarin was not detected, indicating that a fraction of the SNORD27 RNA likely forms a protein complex different from canonical snoRNAs found in the insoluble nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(168 citation statements)
references
References 85 publications
(97 reference statements)
6
161
1
Order By: Relevance
“…This suggests CB regulation of snRNA production can alter competitive balances with other small RNAs to affect splicing. For example, a snoRNA was found that competes with U1 snRNA for a binding site in RNA, leading to mis-splicing for the E2F7 transcription factor [126]. As such, the CB is an important regulator of small RNA expression and function (Figures 2, 3 and 4).…”
Section: Altered Rna Processing By Cajal Bodies Influences Splicing Kmentioning
confidence: 99%
“…This suggests CB regulation of snRNA production can alter competitive balances with other small RNAs to affect splicing. For example, a snoRNA was found that competes with U1 snRNA for a binding site in RNA, leading to mis-splicing for the E2F7 transcription factor [126]. As such, the CB is an important regulator of small RNA expression and function (Figures 2, 3 and 4).…”
Section: Altered Rna Processing By Cajal Bodies Influences Splicing Kmentioning
confidence: 99%
“…These snoRNAs are classified as ‘orphan’ snoRNAs. Recent studies have shown that box C/D snoRNAs not only target rRNA and snRNA but also mRNAs and that they may have functions not related to site-directed methylation of ribose sugars [810]. In particular, fragments derived from snoRNAs (sdRNAs–snoRNAs derived) have been identified that exhibit miRNA-like characteristics and regulate alternative mRNA splicing in several species including mammals [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although our study links the snoRNAs to altered mitochondrial function and ROS production, the precise molecular targets of these snoRNAs responsible for the observed physiological phenotypes remain to be determined. Beyond the predicted 28S and 18S ribosomal RNA targets for these snoRNAs (41), the Rpl13a snoRNAs may also function non-canonically to target mRNAs, given recent studies demonstrating that some snoRNAs target mRNAs (42,43) and our previous observation that the Rpl13a snoRNAs accumulate in the cytoplasm under metabolic stress conditions (12). Our RNAseq analysis suggests that rather than affecting the abundance of potential mRNA targets, the Rpl13a snoRNAs may impact their translation potential.…”
Section: Discussionmentioning
confidence: 71%